Vulnerability and adaptation to climate change of selected community-based forest management areas in Oas, Albay, Philippines - Tapia, Maricel A.; Pulhin, Juan M.; Peras, Rose Jane J. (2014)
Community-based forest management (CBFM) communities have been put at the forefront of forest management following a paradigm shift in forestry, which favors a more participatory approach to bring development to the grassroots. Whilst such intervention is intended to achieve total human development, realities on the ground saw a disparity in the realization of this goal and the 'bundle of responsibilities' bestowed on the upland communities. Achieving human development is further challenged by climate change which poses threats to forest and the delivery of its services, where the livelihoods of upland communities depend. Set at this backdrop, this study assessed the vulnerability and adaptation to climate change of selected CBFM communities in Oas, Albay, Philippines, applying the Adaptation Policy Framework. Data were collected using participatory rural appraisal techniques, household survey, key informant interviews and secondary data collection. Results revealed the high vulnerability of the selected communities to extreme weather events, such as typhoons and El Niño, which translates as well to high vulnerability to climate change. This can be traced to their fragile environments caused by degraded forest ecosystems, high degree of dependence on farming in the absence of alternative livelihoods, and low adaptive capacity due to inadequate basic services. 'Band-aid' or 'bearing the losses' approach to adaptation further aggravated the situation. Though CBFM can be considered a 'no regret' adaptation to climate change, it failed to deliver its promise of ecological sustainability and improved livelihoods in the two communities due to administration and financial issues. Notwithstanding current limitations of CBFM, however, it still remains a promising approach not only in accomplishing its original objectives, but also in reducing vulnerability to climate change. Updating CBFM to respond to future climate and with improvements in its facilitation and implementation aspects, it could prove to be an indispensable strategy for climate change adaptation.
Keywords: Forest management -- Oas (Albay); Forest management -- Oas (Albay) -- Citizen participation; Climate change risk management; Adjustment (Psychology)